The Impact of Technology on Economic Growth: A Analysis of Case Studies In Indonesia - Alam, Syamsu; Jamil, Muh. (Universitas Negeri Makassar, 2023)
In Indonesia, the penetration of technology within government programs has become increasingly prevalent. Technology refers to the application of scientific knowledge for practical purposes, leading to the growth of tools, systems, and processes that enhance human capabilities and address societal needs. The method used in this study is to use qualitative methods using descriptive quantitative and qualitative. Using three steps through literature review, observation, and documentation. literatures on technology and economic growth are reviewed to generate a systematic mapping of concepts. Observational data from the Statistics of Indonesia, and government documents in the form of regulations and performance evidence serve as references for case studies. The Result of this study is Governments play a central role in shaping the trajectory of technological growth through the establishment of policies. The Indonesian government has recognized the importance of innovation in creating progress in the regions and has set regulations to encourage innovation in the regions. The Indeks Inovasi Daerah has been implemented to measure the level of innovation in the regions. Some priority areas in Indonesia that relate to the development of the country’s digital economy and accelarting techology adoption. They are: Accelerating connectivity through infrastructure development, Fostering a capable digital society, Promoting trust in the digital economy, Empowering MSMEs, increasing quality of investment, Advancing digital trasnformation for economic growth, and doing planning and program digitalization with consistency and sustainability.